From genes to clones : introduction to gene technology - Winnacker, Ernst L. (VCH, 1987)
This textbook on gene technology offers for the first time a unified approach to the subject and summarizes the concepts and strategies behind the art of gene cloning. It is the only book available that covers all technical matters. The author, a well-known teacher and scientist, describes the unit operations of gene technology and provides practical guidance on the isolation and characterization of DNA and genes, the development of cloning vectors, and the characterization of recombinant DNA molecules. He also discusses in great detail the development and practical applications of plasmids, bacteriophages, cosmids, phasmids, and eukaryotic viruses as cloning vehicles, along with the respective hosts, i.e., prokaryotes, streptomyces, yeasts, plant cells, and eukaryotes. The book, a completely revised and updated translation of the best-selling German text, leads to the frontiers of current knowledge. Each chapter contains an extensive list of references with the most recent literature up to 1986. The appendix includes information about frequently used host straints, restriction enzymes, restriction maps, sequence data, and the 1986 NIH Guidelines for Research Involving Recombinant DNA Molecules. A very detailed index and more than 400 figures allow the book to be used as a reference manual.